Applications of neutron powder diffraction - Kisi, Erich H.; Howard, Christopher J. (Oxford : Oxford University Press, 2008)
This title covers the theory, practicalities, and the extensive applications of neutron powder diffraction in materials science physics, chemistry, mineralogy and engineering.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Neutrons -- Diffraction; Powders -- Optical properties